Pengaruh Model Pembelajaran Snowball Throwing terhadap Hasil Belajar Matematika Siswa Kelas V SDN 80 Kalibaru Kabupaten Bombana - Abrina Maulidnawati Jumrah; Nurhayati Selvi; Anitawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2021)
Abstrac: The Effect of Snowball Throwing Learning Model on Mathematics Learning Outcomes of Grade V Students of SDN 80 Kalibaru, Bombana Regency. This research aims to find out student learning outcomes by using the snowball throwing learning model in mathematics subjects and find out the influence of the use of the snowball throwing learning model on the mathematics learning outcomes of grade V students at SDN 80 Kalibaru, Bombana Regency. This research uses a quantitative approach with experimental research methods with a type of tru experimental design experimental research. The results of this study showed that mathematics learners after using their learning model snowball throwing model against kels v students of SD N 80 Kalibaru, Bombana district experienced an increase with a mean in posttesstt less high with a mean result obtained of 85.00 compared to the value of the pretest mean result obtained was 68.33. In addition, there is a significant influence after the application of the learning snowball throwing model This is evidenced by the test or independent test untill T-Test is obtained 0.0000 so that the value of 0.0000 < 0.005.